Detection of low urine output by measuring urinary biomarkers - Robert G. Hahn (BMC Nutrition, 2024)
Abstract Background Urine output < 1 L per 24 h is a clinical warning sign that requires attention from hospital staff, who should determine whether the low flow is due to low habitual intake of water or disease-induced dehydration. The incidence of this condition is unclear. Methods A cohort of 20 healthy volunteers (mean age 42 years, range 23–62 years) recorded their food and water intakes daily for 8 days. They also collected and measured all urine and delivered first morning urine samples for analysis of osmolality and creatinine. Optimal cutoffs for these biomarkers to indicate urine output of < 1 L or 15 mL/kg during the preceding 24 h were applied with and without correction for age to cross-sectional data from 1,316 subjects in various clinical settings, including healthy volunteers, preoperative patients, patients seeking acute care at a hospital, and patients receiving institutional geriatric care. Results The urine output amounted to < 1 L during 22 of the 159 evaluable study days and was indicated by urine osmolality > 760 mosmol/kg or urine creatinine > 13 mmol/L, which had sensitivity and specificity of approximately 80%. Days with urine output < 1 L were associated with significantly less intake of both water (–41%) and calories (–22%) compared to other days. Application of age-corrected biomarker cutoffs to the 1,316 subjects showed a stronger dependency of low urine output on age than the clinical setting, occurring in 44% of the 72 participants aged 15–30 years and 18% of the 62 patients aged 90–104 years. Conclusion Biomarkers measured in morning urine of young and middle-aged volunteers indicated urine output of < 1 L with good precision, but the cutoffs should be validated in older age groups to yield reliable results. Trial registrations ISRCTN12215472 at http://www.isrctn.com ; NCT01458678 at ClinicalTrials.gov, and ChiCTR-TNRC-14,004,479 at the chictr.org/en.